SERCA2a: its role in the development of heart failure and as a potential therapeutic target - Fragoso-Medina J; Zarain-Herzberg A (Research Reports in Clinical Cardiology, 2014)
Jorge Fragoso-Medina, Angel Zarain-Herzberg Department of Biochemistry, School of Medicine, National Autonomous University of Mexico, Mexico City, Mexico Abstract: The complexity of heart physiology has delayed the implementation of efficient, feasible, and safe therapies to fight against heart diseases for many years. As knowledge of the precise mechanisms governing cardiac hypertrophy and heart failure development increases, the availability of new therapeutic alternatives also grows. Since the cardiomyocyte physiology deeply depends on the correct calcium handling, many efforts to describe accurately the excitation–contraction coupling process in the heart and the proteins involved have been made. Among the proteins participating in calcium handling, sarco/endoplasmic reticulum Ca2+ adenosine triphosphatase-2a (SERCA2a), whose expression and function is decreased in heart failure, stands out because of its critical role regulating Ca2+ concentration in the cardiomyocyte. The importance of SERCA2a has been reflected in numerous studies aimed to describe its expression and function. Recently, gene therapy to deliver SERCA2a has shown promising results in human clinical trials. This paper reviews the current literature knowledge exploring diverse approaches to rescue SERCA2a expression in heart failure. It also discusses some data suggesting other possible therapies that could improve SERCA2a expression and function in cardiac diseases. Keywords: SERCA2a, cardiac hypertrophy, heart failure, gene therapy, calcium